Assessment of heart rate variability and tone of the autonomic nervous system in puberty-aged children with undifferentiated connective tissue dysplasia. (14th October 2021) - Sidorovich, O V; Elizarova, S Y U; Khizhnyak, A V; Kuznetsova, N A; Prosova, E E
Abstract: : Within the framework of the research into pathological conditions and syndromes associated with undifferentiated connective tissue dysplasia (UCTD), an emphasis needs to be placed on the changes in heart rhythm. In puberty, the severity of neurovegetative disorders caused by the presence of UCTD might increase manifold. The features of heart rate variability (HRV) in pubertal children against the background of UCTD have been studied insufficiently and require more detailed analysis. This study aims to assess heart rate variability and tone of the autonomic nervous system (ANS) in puberty-aged children with UCTD. Two groups of children were examined, with methods including electrocardiography and cardiointervalography. The main group consisted of 36 puberty-aged children with UCTD, the control group consisted of 30 healthy children. ANS tone was assessed based on the HRV. In the control group of children aged 11, the value of variation range (VR) was 0.18±0.4, mode amplitude (MA) 35.2±2.4, stress index (IN) 72.8±4.3, which corresponds to the state of vegetative balance. As the puberty progresses, the state of eutonia is replaced by the activation of the sympathetic division of the ANS, which becomes most pronounced at the age of 13 years. In the control group of children aged 13, the value of VR was 0.08±0.02, MA 61.7±2.1, SI 210.6±8.6, which corresponds to moderate sympathicotonia. By the end of puberty, in healthy children, the severity of sympathetic activation begins to decrease, and at the age of 15 years, vegetative balance is again observed. However, this pattern is violated in children with UCTD. Upon entering puberty, moderate activation of the sympathetic division of the ANS is already observed in children with UCTD. At the age of 11 years in this group, the value of VR is 0.06±0.02, MA 72.4±3.1, SI 211.2±8.6. At the age of 13, pronounced sympathicotonia is observed, which is confirmed by the values of VR - 0.04±0.01, MA 80.2±4.3 and SI 34.3±14.7. By the end of puberty in children with UCTD, in contrast to the control group, the analyzed parameters indicate not an equilibrium of the ANS, but the predominance of parasympathetic activation. The research provides an insight into heart rate variability in puberty-aged children with UCTD. It was established that healthy children enter puberty in a state of equilibrium of the autonomic nervous system, which in the middle of puberty is replaced by moderate sympathicotonia, and then returns to its original values. Children with the presence of UCTD enter puberty with moderately pronounced sympathicotonia, which gradually increases to pronounced values and is replaced by moderate vagotonia. FUNDunding Acknowledgement: Type of funding sources: None.